Vivendo como São Francisco de Assis: um estudo etnográfico sobre a Fraternidade Católica Toca de Assis - Nayara Alvim Silva (2013)
This study aims to analyze the changes in the Fraternidade Católica Filhos e Filhas da Pobreza do Santíssimo Sacramento, best known as Toca de Assis. Toca de Assis, in just eighteen years of existence has acquired over a thousand consecrated who lived in fraternal houses scattered in all around Brazil and some other countries of the world. In front this vertiginous growth, the Catholic Church came into dispute to restructure the experience of the sacred of that institution and mold it into something increasingly restrained and allowed by the clergy. There was an attempt to domesticate the sacred. Faced multiple specificities of the charisma toqueiro, the Archdiocese of Campinas took control of Toca de Assis after the expulsion of their founder, alleging that members of the fraternity needed to new directions. With this, the result so far is the closing of several houses and waiver of various religious who left their families to identify with the charism and spirituality toqueira, seen by many as being radical because it is based on three pillars of religious consecration, namely, chastity, obedience and poverty